343 Effect of Ruminally-Protected Lysine Supplementation to Limit-fed Growing Cattle on Growth and Subsequent Finishing Performance. (21st September 2022) - Hazlewood, Kathryn J; Grant, Madeline S; Blasi, Dale A; Ducharme, Gary A; Titgemeyer, Evan C
Abstract: Lysine may be limiting for cattle fed diets based on corn products. Our objective was to supplement ruminally protected lysine to cattle limit-fed a corn-based diet during the growing phase and assess performance during growing and subsequent finishing phases. The 77-d growth trial used 338 crossbred steers allocated to 32 pens limit-fed 2.4% of body weight daily. Steers were implanted (40 mg trenbolone acetate, 8 mg estradiol) at trial initiation. Diets contained 39.5% corn grain, 40% wet corn gluten feed, 13% hay, and 7.5% supplement. Treatments included: no supplemental amino acids (control), 3 g/d metabolizable lysine from Smartamine ML (Adisseo, Alpharetta, GA; Lys-3), 6 g/d metabolizable lysine from Smartamine ML (Lys-6), and supplemental blood meal (Aadvantage; Perdue Agribusiness, Kings Mountain, NC) at 0.89% of dietary dry matter plus 2 g/d metabolizable methionine from Smartamine M (BM). Individual body weights were measured on d 0 and 77. After 77 d, cattle were shipped to a commercial feedlot, commingled in 2 pens, fed a common diet for 185 or 206 d, and slaughtered commercially. Performance during finishing was measured using carcass data from the slaughter facility. During the growing phase, Lys-3 tended to improve average daily gain by 0.11 kg/d (P = 0.12) and feed efficiency (P = 0.08) compared with control. During finishing, Lys-6 tended to have daily gains 0.05 kg/d greater than control and Lys-3 (P = 0.17). Carcass weights were 7.1 and 3.4 kg heavier than control for Lys-6 and Lys-3, respectively. BM did not affect performance during the growing or finishing period and resulting carcass weight. Ruminally protected lysine supplementation during the growing phase tended to improve performance of cattle during growing and/or finishing phases, as well as carcass weights.